2001
DOI: 10.2135/cropsci2001.4151625x
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme Diversity in North American Cultivated Red Clover

Abstract: per locus, 53.3% polymorphic loci, and the amount of among-population genetic variation was much smaller Red clover (Trifolium pratense L.) is a forage legume with considthan the within-population variation. The objective of erable economic importance in world agriculture. Knowledge of the this study was to assess genetic diversity in North Ameriamount and distribution of genetic variability within a species is vital to breeders and geneticists when selecting breeding germplasm. The can red clover cultivars on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 11 publications
(9 reference statements)
4
29
3
Order By: Relevance
“…For wild red clover populations Semerikov et al (2002) found H e values that ranged from 0.128 to 0.196 and P ranging from 0.41 to 0.52 and Mosjidis et al (2003) reported P= 74, A = 1.7 and H e = 0.323. For cultivated red clover Kongkiatngam et al (1995) reported H e values ranging from 0.10 to 0.12 in a comparison of two different cultivars and for 34 cultivars of red clover Yu et al (2001) observed mean values of P = 74, A = 1.59 and H e = 0.285. For the same core collection Mosjidis and Klingler (2006) reported average mean of P = 77.5, A = 1.66 and H e = 0.316.…”
Section: Isozyme Allelic Frequency Datamentioning
confidence: 98%
See 3 more Smart Citations
“…For wild red clover populations Semerikov et al (2002) found H e values that ranged from 0.128 to 0.196 and P ranging from 0.41 to 0.52 and Mosjidis et al (2003) reported P= 74, A = 1.7 and H e = 0.323. For cultivated red clover Kongkiatngam et al (1995) reported H e values ranging from 0.10 to 0.12 in a comparison of two different cultivars and for 34 cultivars of red clover Yu et al (2001) observed mean values of P = 74, A = 1.59 and H e = 0.285. For the same core collection Mosjidis and Klingler (2006) reported average mean of P = 77.5, A = 1.66 and H e = 0.316.…”
Section: Isozyme Allelic Frequency Datamentioning
confidence: 98%
“…A breeding program aimed at the creation of regionally adapted cultivars and the development of local seed production was therefore initiated at the Federal University of Rio Grande do Sul (UFRGS). Many studies using morphologic (Kouamé Analysis of genetic diversity in the core collection of red clover (Trifolium pratense) with isozyme and RAPD markers and Quesenberry 1993, Christie andChoo 1991, Bulinska-Radomska 2000), molecular (Kongkiatngam et al 1995, Campos-de-Quiroz and Ortega-Klose 2001, Kölliker et al 2003, Greene et al 2004, Herrmann et al 2005, Sato et al 2006) and biochemical traits (Hagen and Hamrick 1998, Yu et al 2001, Mosjidis and Klingler 2006 have demonstrated high genetic diversity, both among and within red clover populations. In view of the current interest in sustainable agriculture, red clover seems promising, since cultivated legumes play an important role in atmospheric N fixation and air and water pollution reduction (Rochon et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many works using morphologic (Christie & Choo, 1991;Kouamé & Quesenberry, 1993), molecular (Greene et al, 2004;Sato et al, 2005;Dias et al, 2008a) and biochemical traits (Yu et al, 2001;Mosjidis & Klinger, 2006) have showed the high genetic diversity present in this species. All red clovers may be grouped into three divisions corresponding to early, medium and late maturity types (Bird, 1948;Taylor & Smith, 1995).…”
Section: Introductionmentioning
confidence: 93%